2020
DOI: 10.2478/fv-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Studies of αSMA in the Epididymis of African Four-Toed Hedgehog (Atelerix albiventris)

Abstract: The epididymis plays an important role in sperm maturation, storage, transport and in the secretion of enzymes and proteins into the tubular lumen. In this study, we examined the histology, microstereology and immunohistochemical localization of alpha smooth muscle (αSMA) in the three regions of the epididymis of the African four-toed hedgehog (Atelerix albiventris). Ten adult males were captured from the wild in Ibadan, Nigeria, between May and October, 2016. The animals were euthanized and the epididymis (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The spatial distribution of S-100 protein in the testis in the African striped ground squirrel from the present study is comparable to that of other mammals. The immunoreaction in the vascular endothelium is same as in the pine vole, rabbit and African four-toed hedgehog by Czykier et al (2000), Abd-Elmaksoud et al (2014) and Olukole et al (2020), respectively. However, while the immunoreaction of S-100 in the Leydig cells in the African striped ground squirrel in the present study was also reported in other rodents such as the Wistar rat, bank vole (and mouse) and African four-toed hedgehog by Amselgruber et al (1994), Czykier et al (2000) and Olukole et al (2020), respectively, it was unreactive in the Leydig cells of lagomorphs such as the rabbit (Abd-Elmaksoud et al (2014).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The spatial distribution of S-100 protein in the testis in the African striped ground squirrel from the present study is comparable to that of other mammals. The immunoreaction in the vascular endothelium is same as in the pine vole, rabbit and African four-toed hedgehog by Czykier et al (2000), Abd-Elmaksoud et al (2014) and Olukole et al (2020), respectively. However, while the immunoreaction of S-100 in the Leydig cells in the African striped ground squirrel in the present study was also reported in other rodents such as the Wistar rat, bank vole (and mouse) and African four-toed hedgehog by Amselgruber et al (1994), Czykier et al (2000) and Olukole et al (2020), respectively, it was unreactive in the Leydig cells of lagomorphs such as the rabbit (Abd-Elmaksoud et al (2014).…”
Section: Discussionmentioning
confidence: 59%
“…The immunoreaction in the vascular endothelium is same as in the pine vole, rabbit and African four-toed hedgehog by Czykier et al (2000), Abd-Elmaksoud et al (2014) and Olukole et al (2020), respectively. However, while the immunoreaction of S-100 in the Leydig cells in the African striped ground squirrel in the present study was also reported in other rodents such as the Wistar rat, bank vole (and mouse) and African four-toed hedgehog by Amselgruber et al (1994), Czykier et al (2000) and Olukole et al (2020), respectively, it was unreactive in the Leydig cells of lagomorphs such as the rabbit (Abd-Elmaksoud et al (2014). This presence of S-100 in vasculature of blood vessels have been attributed to the protective role of the protein against mitochondrial dysfunction and cell death due to intracellular calcium overload (Orrenius et al, 2003).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations